Engineering Vulnerability : In Pursuit of Climate Adaptation - Vaughn, Sarah E., 1983- (Book collections on Project MUSE., 2022)
"Engineering Vulnerability is an ethnography of climate adaptation in Guyana, where different portions of the population experience and understand environmental threats differently. Sarah E. Vaughn focuses on the collaborations between state experts and citizens following the 2005 flood that left 75 percent of the country's population stranded in water, and highlights how government engineers and local villagers each had knowledge that was formed through their racial positioning in the country. While climate adaptation is often seen as primarily a state project, especially in relation to disaster, Vaughn shows that it cannot be understood apart from the multiple histories and relations to the environment that differently position citizens and experts who must work together in the face of climate vulnerability"--